The Occurrence of Gallbladder Carcinoma in Yemeni Patients Undergoing Cholecystectomy in Two Hospitals - Al-Bahlooli, Saeed H.; Soltan, Ahmed S.; Al-Malahi, Ahmed (Thamar University Journal of Natural & Applied Sciences, 2023)
Background: Primary cancer of the gallbladder has wide geographical, ethnic and cultural variations with poor prognosis. Currently, there is no study about gallbladder carcinoma in Yemen. The aim is to detect the occurrence of gallbladder carcinoma in Yemeni patients undergoing cholecystectomy. Patients and Methods: A descriptive retrospective study of data of 940 patients operated for gallstones in two university hospitals in Yemen between 2002 and 2006 was carried out with respect to results of histopathological analysis of gallbladder specimens. There were 872 women and 68 men. Patients who have no histopathological reports in their files were excluded. Histopathological reports of 838 patients were retrospectively investigated for gallbladder malignancy. Results: Gallbladder carcinoma was detected in 4 female patients of median age 66 years. No male patient was affected. Adenocarcinoma was the variety found in all four cases. All four patients with gallbladder cancer have history of longstanding gallstone disease. Conclusion: The study supports the hypothesis that gallbladder carcinoma is rare and mostly affects elder women with long-standing gallbladder stones. The occurrence of gallbladder carcinoma in the targeted sample is significantly less than that of the western countries. Cooperation between surgeon, sonographist and histopathologist is strongly advised, particularly when gallbladder malignancy is suspected